Catalytic Study of the Partial Oxidation Reaction of Methanol to Formaldehyde in the Vapor Phase - Mohammad Hasan Peyrovi; Nastaran Parsafard; Hosein Hasanpour (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
In the present work, several parameters affecting on the catalytic behavior were studied in the process of partial oxidation of methanol to formaldehyde, such as: Mo/Fe ratio in unsupported catalysts, weight percent of the metallic phase in the supported catalysts, the effect of different supports, the method of Mo-Fe deposition on the supports, and the stability of the prepared catalysts against coke. These catalysts were characterized by X-ray diffraction (XRD), Fourier Transform Infra Red (FT-IR), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), N2 adsorption-desorption, and Atomic Adsorption Spectroscopy (AAS) methods. The best results (the methanol conversion = 97 % and formaldehyde selectivity = 96 %) were obtained for Mo-Fe/g-Al2O3 prepared by co-precipitation method with Mo/Fe = 1.7, 50 wt.% of Fe-Mo phase, 2 mL/h methanol flow rate, and 120 mL/min air flow rate at 350 oC.